2009
DOI: 10.1007/s11664-009-0908-y
|View full text |Cite
|
Sign up to set email alerts
|

N Doping and Al-N Co-doping in Sol–Gel ZnO Films: Studies of Their Structural, Electrical, Optical, and Photoconductive Properties

Abstract: We have studied the structural, electrical, optical, and optoelectronic properties of N-doped and Al-N co-doped ZnO films grown by sol-gel technique. Both the undoped and doped films have a hexagonal wurtzite-type structure. The undoped film shows a very low electron concentration. The N-doped film exhibits an anomalous conduction type, while the Al-N co-doped film shows relatively stable p-type conduction. Though the transparency in the visible region is retained in the doped films, its optical qualities are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…High resistivity was observed from the films without co-doping. The films co-doped with aluminium possess an acceptable resistivity with Hole concentration in the 10 17 cm −3 and resistivity range between 45 and 62 cm 2 /V s. These results correlate well with data published by Ge and Dutta [20,33]. Fig.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…High resistivity was observed from the films without co-doping. The films co-doped with aluminium possess an acceptable resistivity with Hole concentration in the 10 17 cm −3 and resistivity range between 45 and 62 cm 2 /V s. These results correlate well with data published by Ge and Dutta [20,33]. Fig.…”
Section: Resultssupporting
confidence: 90%
“…The EDX data also shows that the sputtered film had incorporated most nitrogen and the ZnO:Al:N (NH 4 OH) the least. Dutta et al [33] has suggested that NH 3 readily escapes from ammoniac solution, unless the experiment is conducted under airtight condition. During the sputtering process, the chamber had been evacuated into high vacuum (10 −6 Torr).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the biggest challenge to achieve the ZnO-based optoelectronic devices is the difficulty to fabricate reliable p-type ZnO. In previous studies, many efforts focuses on doping ZnO with N [12], P [13], As [15] and Al-N [16] co-doped to achieve p-type conductivity. These dopants are used to alter the type of conductivity as well as the electrical and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Group V elements have been shown to be the most promising dopants for producing p-type ZnO. According to earlier theoretical calculations of the electronic band structure, N is predicted to be the best candidate for producing a shallow acceptor level in ZnO [2], because the ionic radii of nitrogen and oxygen are comparable. Therefore, nitrogen atoms can replace oxygen with little lattice change.…”
Section: Introductionmentioning
confidence: 99%